Autobiographical memory in depression. - Williams, J; Scott, J (1988)
Recent research has shown that suicidal patients are not only biased in the speed with which they can remember positive and negative events from their past, but that they also find it more difficult to be specific in their memories. That is, they tend to recall sequences of events, or time periods, rather than single episodes. This tendency has been found to be more evident with positive than with negative events. This paper examines whether the same phenomenon can be observed in patients with a diagnosis of primary Major Depressive Disorder. Twenty depressed patients and twenty matched controls were presented with positive and negative cue words and asked to retrieve specific personal memories. Results showed that depressives (unlike controls) took longer to respond to positive than to negative cues. In addition, the depressed patients were less specific in their memories, especially in response to positive cues. These results are explained within a 'descriptions' theory of autobiographical memory, and the remedial implications are discussed.